In Vivo Relevance of a Biphasic In Vitro Dissolution Test for the Immediate Release Tablet Formulations of Lamotrigine - Tuba Incecayir; Muhammed Enes Demir (MDPI AG, 2023)
Biphasic in vitro dissolution testing is an attractive approach to reflect on the interplay between drug dissolution and absorption for predicting the bioperformance of drug products. The purpose of this study was to investigate the in vivo relevance of a biphasic dissolution test for the immediate release (IR) formulations of a Biopharmaceutics Classification System (BCS) Class II drug, lamotrigine (LTG). The biphasic dissolution test was performed using USP apparatus II with the dual paddle modification. A level A in vitro-in vivo correlation (IVIVC) was constructed between the in vitro partition into the octanol and absorption data of the reference product. A good relation between in vitro data and absorption was obtained (r2 = 0.881). The one-compartment open model was introduced to predict the human plasma profiles of the test product. The generic product was found to be bioequivalent to the original product in terms of 80-125% bioequivalence (BE) criteria (85.9-107% for the area under the plasma concentration curve (AUC) and 82.7-97.6% for the peak plasma concentration (Cmax) with a 90% confidence interval (CI)). Overall, it was revealed that the biphasic dissolution test offers a promising ability to estimate the in vivo performance of IR formulations of LTG, providing considerable time and cost savings in the development of generic drug products.